2022
DOI: 10.1155/2022/8564818
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Statin and Risk of Age-Related Macular Degeneration: A Systematic Review and Meta-Analysis

Abstract: Introduction and Aim. Age-related macular degeneration (AMD) is one of the leading causes of blindness and visual defect, particularly in elderly people across the world. This meta-analysis aimed at investigating the relationship between statin and the risk of AMD. Methods. Web of Science, PubMed, and Scopus databases were searched for articles that addressed the relationship between statin consumption and risk of AMD. The pooled odds ratio (OR) and 95% confidence interval (CI) were calculated using a random-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…[28] One recent review maintains the potentially beneficial role of statins in AMD while underscoring the complexity of underlying associations, [53] , while two others could not confirm an association. [54,55] Our study supports the body of evidence suggesting a beneficial association with AMD and represents, to our knowledge, the first study metaanalyzing individual level data from various population-and hospital-based studies instead of meta-analyzing published aggregated results only. Yet, further longitudinal data are needed to confirm our findings, which are inherently limited by using cross-sectional data only and cannot infer causality.…”
Section: Discussionsupporting
confidence: 81%
“…[28] One recent review maintains the potentially beneficial role of statins in AMD while underscoring the complexity of underlying associations, [53] , while two others could not confirm an association. [54,55] Our study supports the body of evidence suggesting a beneficial association with AMD and represents, to our knowledge, the first study metaanalyzing individual level data from various population-and hospital-based studies instead of meta-analyzing published aggregated results only. Yet, further longitudinal data are needed to confirm our findings, which are inherently limited by using cross-sectional data only and cannot infer causality.…”
Section: Discussionsupporting
confidence: 81%
“…In general, this meta-analysis supported that statins had a protective role for both early and exudative AMD [ 46 ]. However, a recent systematic review and meta-analysis that aimed to link statins and AMD led to a different conclusion [ 47 ]. Researchers reviewed a total of 22 studies, with 2,063,195 participants, 15.2% of whom were diagnosed with AMD.…”
Section: Discussionmentioning
confidence: 99%
“…The OR of AMD in those that received statins were 0.92 (95% CI; 0.75–1.13, p = 0.440) in case-control studies, 0.95 (95% CI; 0.82–1.09, p = 0.458) in cohort studies, and 0.951 (95% CI; 0.59–1.53, p = 0.831) in cross-sectional studies. This meta-analysis showed that statin therapy has no positive or negative impact on AMD development [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve reduced cholesterol biosynthesis, it is necessary to inhibit the key rate-limiting enzymes in the synthesis pathway. Although studies have shown that statins do not increase or reduce the risk of AMD, 193,194 a recent study has demonstrated that simvastatin can inhibit the biosynthesis of retinal cholesterol, which is valuable for future clinical research on statins as potential treatment methods for AMD. 195 Additionally, DHCR24 inhibitors can also reduce the TC content in the retina.…”
Section: Role Of Cholesterol Metabolism Regulationmentioning
confidence: 99%